Evaluating school disaster preparedness: A comparative study between urban and rural areas in Indonesia - Nurdiansyah, Muhamad Irfan; Nurwati, Dewi (Priviet Social Sciences Journal, 2025)
Indonesia is among the countries most vulnerable to natural disasters, positioning school preparedness as a strategic priority in national disaster risk reduction (DRR) initiatives. This study aimed to assess the level of disaster preparedness in schools using a qualitative approach based on a secondary literature review. The data are drawn from peer-reviewed journals, official government publications, and reports from accredited humanitarian organizations published between 2018 and 2024. This study employs a dual evaluative framework, the School Disaster Resilience Index (SDRI) developed by UNESCO, and the indicators of the Disaster-Resilient Education Unit (SPAB), as mandated by Regulation of the Minister of Education and Culture No. 33 of 2019. The analysis focuses on six core dimensions: school infrastructure, disaster training, integration of DRR into the curriculum, community participation, use of technology, and cultivation of a safety culture within schools. The findings highlight the significant disparities between urban and rural schools, especially regarding access to resources, institutional support, and technological integration. Although rural schools exhibit strong community engagement and the application of local wisdom, they remain behind in terms of structural and systemic preparedness. The novelty of this study lies in its integration of two evaluative models and its proposal for a disaster risk education curriculum tailored to the local context. These results are expected to contribute to the formulation of more inclusive and adaptive disaster education policies in Indonesia, particularly by informing government agencies such as the Ministry of Education and Culture (Kemendikbud), the National Disaster Management Agency (BNPB), regional disaster management bodies (BPBD), and non-governmental organizations involved in school-based disaster risk reduction efforts.